Pipeline provenance for cloud‐based big data analytics. (5th September 2019) - Wang, Ruoyu; Sun, Daniel; Li, Guoqiang; Wong, Raymond; Chen, Shiping
Summary: Provenance is information about the origin and creation of data. In data science and engineering related with cloud environment, such information is useful and sometimes even critical. In data analytics, it is necessary for making data‐driven decisions to trace back history and reproduce final or intermediate results, even to tune models and adjust parameters in a real‐time fashion. Particularly, in cloud, users need to evaluate data and pipeline trustworthiness. In this paper, we propose a solution: LogProv, toward realizing these functionalities for big data provenance, which needs to renovate data pipelines or some of big data software infrastructure to generate structured logs for pipeline events, and then stores data and logs separately in cloud space. The data are explicitly linked to the logs, which implicitly record pipeline semantics. Semantic information can be retrieved from the logs easily since they are well defined and structured beforehand. We implemented and deployed LogProv in Nectar Cloud, * associated with Apache Pig, Hadoop ecosystem, and adopted Elasticsearch to provide query service. LogProv was evaluated and empirically case studied. The results show that LogProv is efficient since the performance overhead is no more than 10%; the query can be responded within 1 second; the trustworthiness is marked clearly; and there is no impact on the data processing logic of original pipelines.